The Role of Religious Cooperation in Negative Emotions Experienced During Covid-19 - Okan, Nesrullah; Oren, Aytac (Ataturk Univ, 2021)
This study was carried out to determine the negative emotions that arise during the Covid-19 process, to determine what kind of coping styles people use against the negative psychological factors, and to see how religion affects coping. In the research, answers were sought to three basic questions: In the first question, what kind of adverse psychological problems people experienced with the pandemic; in the second question, what type of coping styles are developed against the negative psychological situations they encounter; In the third question, an answer was sought on the position of negative coping among individuals' coping styles. For this purpose, data were obtained from 19 male and 41 female participants studying at the undergraduate level in different faculties, who themselves or someone from their close circles had Covid-19 experiences. The data obtained within the scope of the research were converted into text and analyzed with the help of Maxqda 20 Package Program. As a result of the analysis, various codes, sub-themes, and themes were reached. When the effects are examined, it is seen that individuals generally experience many negative emotions such as anxiety, fear, hopelessness, stress, fatigue, and depression. However, it has been concluded that individuals use religious coping the most against these adverse situations.
Keywords: Psychology of Religion; Covid-19; Negative Emotions; Religious Coping; Qualitative Research